Aesthetics of interaction in digital art - Kwastek, Katja (The MIT Press, 2015)
"Since the 1960s, artworks that involve the participation of the spectator have received extensive scholarly attention. Yet interactive artworks using digital media still present a challenge for academic art history. In this book, Katja Kwastek argues that the particular aesthetic experience enabled by these new media works can open up new perspectives for our understanding of art and media alike. Kwastek, herself an art historian, offers a set of theoretical and methodological tools that are suitable for understanding and analyzing not only new media art but also other contemporary art forms. Addressing both the theoretician and the practitioner, Kwastek provides an introduction to the history and the terminology of interactive art, a theory of the aesthetics of interaction, and exemplary case studies of interactive media art.